KESTABILAN SOSIAL DALAM PERSPEKTIF ISLAM (Tinjauan Sejarah Gender) (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
This paper contains about social stability in the Islamic view. Today gender is veryinteresting to study, so that gave birth to some of the opinions that have an impact on the role ofmen and women have in common demands, but on the other hand require women to contributeto social life. This becomes very contrary to the presence of women in equal social life, in otherwords women and men should have the same role. Demands the same role between men andwomen have an impact on the state of social life that looks at the present time, though not as themain factor of social conflict, but can not be released that gender equality demands of the sociallife is also somewhat due to loss of the role that should be become obligatory for women andmen. Islamic religion has succeeded in giving an answer to the issue of gender, how in Islam doesnot look sharp distinction between men and women, the role of men and women already evidentin Islam. The division of roles of men and women adapted to the nature of which is owned bymen and women. All of these provisions is based on the glasses Allah, who knows everything.Key word: social stability, Islam and gender